Nutrients and perinatal depression: a systematic review - Sparling, Thalia M.; Nesbitt, Robin C.; Henschke, Nicholas; Gabrysch, Sabine (Journal of nutritional science, 2017)
Abstract: Pregnancy and lactation deplete nutrients essential to the neurotransmission system. This may be one reason for the increased risk of depression during the perinatal period. The objective of the present review was to systematically review the literature and summarise evidence on whether blood nutrient levels influence the risk of perinatal depression. PubMed, EMBASE and CINAHL databases were searched for studies of any design. A total of twenty-four articles of different designs were included, representing 14 262 subjects. We extracted data on study population, depression prevalence, nutrients examined, deficiency prevalence, timing of assessment, reporting, analysis strategy and adjustment factors. In all, fourteen studies found associations of perinatal depression with lower levels of folate, vitamin D, Fe, Se, Zn, and fats and fatty acids, while two studies found associations between perinatal depression and higher nutrient levels, and eight studies found no evidence of an association. Only ten studies had low risk of bias. Given the methodological limitations and heterogeneity of study approaches and results, the evidence for a causal link between nutritional biomarkers and perinatal depression is still inconclusive. High-quality studies in deficient populations are needed.